2006
DOI: 10.1007/s10681-006-9208-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting gene × environmental effects on wheat yields via QTL and physiological analysis

Abstract: Crops frequently display genotype · environment interaction for yield and enduse quality in response to different environments, particularly when stresses such as water limitation and temperature are components of the interaction. Plant breeders usually exploit this variation via phenotypic selection to develop varieties with both general and specific adaptation. However the individual genes and physiological processes underlying the basis of general and specific adaptation have rarely been elucidated. We are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 6 publications
3
92
0
8
Order By: Relevance
“…The DH populations and genetics maps used in this study were generated as was described previously (Snape et al, 2007;Griffiths et al, 2009) and summarized in Table 1. Specifically, they are as follows: Avalon 3 Cadenza (AxC), Beaver 3 Soissons (BxS), Shamrock 3 Shango (SxS), Spark 3 Rialto (SpxR), Malacca 3 Charger (MxC), and Savannah 3 Rialto (SaxR).…”
Section: Genetic Resources and Field Trialsmentioning
confidence: 99%
“…The DH populations and genetics maps used in this study were generated as was described previously (Snape et al, 2007;Griffiths et al, 2009) and summarized in Table 1. Specifically, they are as follows: Avalon 3 Cadenza (AxC), Beaver 3 Soissons (BxS), Shamrock 3 Shango (SxS), Spark 3 Rialto (SpxR), Malacca 3 Charger (MxC), and Savannah 3 Rialto (SaxR).…”
Section: Genetic Resources and Field Trialsmentioning
confidence: 99%
“…In bread wheat, QTLs for stem reserve, water-soluble carbohydrates (WSC) remobilization and leaf senescence have been reported across well-watered and waterstressed conditions (Snape et al 2007 ;Rebetzke et al 2008 ;Bennett et al 2012 ;Zhang et al 2015 ). Although these studies showed an important role for WSC in assuring stable yield and grain size, Rebetzke et al ( 2008 ) concluded that the small effects of many independent WSC QTLs may limit their direct use for MAS.…”
Section: Qtls For Carbohydrate Accumulation and Relocationmentioning
confidence: 99%
“…Although these studies showed an important role for WSC in assuring stable yield and grain size, Rebetzke et al ( 2008 ) concluded that the small effects of many independent WSC QTLs may limit their direct use for MAS. A combined QTL analysis for yield of several wheat populations evaluated across different environments and seasons enabled Snape et al ( 2007 ) to identify QTLs showing stable and differential expression across irrigated and non-irrigated conditions. Variation for stem water-soluble carbohydrate reserves was associated with the chr.…”
Section: Qtls For Carbohydrate Accumulation and Relocationmentioning
confidence: 99%
See 2 more Smart Citations